Association between sociodemographic factors and noncavitated and cavitated caries lesions in 8- to 12-year-old Mexican schoolchildren. Issue 25 (25th June 2021) - García Pérez, Alvaro; González-Aragón Pineda, Alvaro Edgar; Rosales Ibáñez, Raúl; Rodríguez Chávez, Jaqueline Adelina; Cuevas-González, Juan Carlos; Pérez Pérez, Nora Guillermina; Villanueva Gutiérrez, Teresa
Abstract : Abstract: The aim of this study was to evaluate the association between sociodemographic factors and noncavitated and cavitated caries lesions in Mexican schoolchildren. This cross-sectional study was conducted in 2020 on 8-to-12-year-old schoolchildren of different socioeconomic status (SES). The caries was evaluated using ICDAS II, SES was evaluated using three categories---a high, middle, or low-income level---of the CONAPO. Multinomial logistic regression analyses were performed in order to ascertain the associations between socioeconomic factors and noncavitated and cavitated caries lesions. The prevalence of noncavitated lesions was 38.0% and cavitated lesions was 43.4% in permanent dentition. In all the samples, 50.6% of schoolchildren had poor oral hygiene. About 52.5% of the mothers and 64.7% of the fathers had less than 9 years of education. Schoolchildren with a low-income level have more cavitated lesions (ICDAS II 4–6) than schoolchildren with high-income level (56.3% vs 15.8%, P  = .009). The multinomial logistic regression models showed that mother's level of education <9 years and low-income level were significantly associated with cavitated caries lesions (ICDAS II 4–6), [odds ratio = 1.79 (1.17 – 2.75); P  = .007], [OR = 2.21 (1.23 – 3.97); P  = .008], respectively. The socioeconomic level was not associated with noncavitated caries lesions (ICDAS II 1–3). An association was found between the presence of cavitated caries lesions and the subject's mother's level of education and a low-income level. Socioeconomic factors were found to be associated with inequalities in caries distribution in the age group studied.